Development and Validation of the Short Version of the Reflux Symptom Score: Reflux Symptom Score–12. (21st July 2020) - Lechien, Jerome R.; Bobin, Francois; Rodriguez, Alexandra; Dequanter, Didier; Muls, Vinciane; Huet, Kathy; Harmegnies, Bernard; Crevier‐Buchman, Lise; Hans, Stéphane; Saussez, Sven; Carroll, Thomas L.
Abstract : Objective: To develop and validate a short version of the Reflux Symptom Score—the 12‐question Reflux Symptom Score–12 (RSS‐12)—for patients with laryngopharyngeal reflux disease (LPR). Study Design: Prospective study. Setting: Multicenter academic hospitals. Methods: Patients with LPR diagnosed via multichannel intraluminal impedance pH monitoring were enrolled from 3 European hospitals. Healthy individuals completed the study. Individuals completed the Reflux Symptom Score, Reflux Symptom Index (RSI), and Voice Handicap Index (VHI) at baseline and 3 months posttreatment. The Reflux Symptom Score was completed twice within a 7‐day period to assess test‐retest reliability. Cronbach's α was used for assessing internal consistency. The RSS‐12 was developed and validity assessed through a comparison of the RSS‐12, RSI, and VHI. Responsiveness to change was evaluated through the pre‐ to posttreatment evolution of the RSS‐12 total score. Receiver operating characteristic analysis was used to determine the RSS‐12 threshold that is suggestive of LPR. Results: The RSS‐12 was characterized by high test‐retest reliability ( r s = 0.956) and adequate internal consistency reliability (α = 0.739). The RSS‐12 was significantly correlated with the RSI ( r s = 0.845), suggesting high external validity. The RSS‐12 total and item scores were significantly higher in patients with LPR as compared with healthy individuals ( P =. 001), supporting high internal validity. RSS‐12, VHI, and RSI significantly improved throughout treatment. Regarding the receiver operating characteristic curve, an RSS‐12 score >11 is suggestive of LPR, exhibiting a sensitivity of 94.5% and a specificity of 86.2%. Conclusion: The RSS‐12 is a shorter, reliable, and valid self‐administered patient‐reported outcome measure questionnaire that can be used in the outpatient setting to suggest and monitor LPR.